2014
DOI: 10.1137/130934696
|View full text |Cite
|
Sign up to set email alerts
|

The Stability of Localized Spot Patterns for the Brusselator on the Sphere

Abstract: In the singularly perturbed limit of an asymptotically small diffusivity ratio ε 2 , the existence and stability of localized quasi-equilibrium multispot patterns is analyzed for the Brusselator reactiondiffusion model on the unit sphere. Formal asymptotic methods are used to derive a nonlinear algebraic system that characterizes quasi-equilibrium spot patterns and to formulate eigenvalue problems governing the stability of spot patterns to three types of "fast" O(1) time-scale instabilities: self-replication,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
143
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(147 citation statements)
references
References 48 publications
4
143
0
Order By: Relevance
“…This analysis is an extension to the analysis performed in [4], where it was shown that a 1-D localized stripe pattern of active-ROP in a 2-D domain will, generically, exhibit breakup into spatially localized spots. To analyze the subsequent dynamics and stability of these localized spots in the presence of the auxin gradient, we will extend the hybrid asymptotic-numerical methodology developed in [25,35] for prototypical RD systems with spatially homogeneous coefficients. This analysis will lead to a novel finite-dimensional dynamical system characterizing slow spot evolution.…”
Section: Parameter Set a Parameter Set Bmentioning
confidence: 99%
See 3 more Smart Citations
“…This analysis is an extension to the analysis performed in [4], where it was shown that a 1-D localized stripe pattern of active-ROP in a 2-D domain will, generically, exhibit breakup into spatially localized spots. To analyze the subsequent dynamics and stability of these localized spots in the presence of the auxin gradient, we will extend the hybrid asymptotic-numerical methodology developed in [25,35] for prototypical RD systems with spatially homogeneous coefficients. This analysis will lead to a novel finite-dimensional dynamical system characterizing slow spot evolution.…”
Section: Parameter Set a Parameter Set Bmentioning
confidence: 99%
“…However, depending on the parameter regime, these localized patterns can also exhibit fast O(1) time-scale instabilities, leading either to spot creation or destruction. For prototypical RD systems such as the Gierer-Meinhardt, Gray-Scott, Schnakenberg, and Brusselator models, the slow dynamics of localized solutions and the possibility of self-replication and competition instabilities, leading either to spot creation or destruction, respectively, have been studied using a hybrid asymptotic-numerical approach in [26,35]. In addition, in the large inhibitor diffusion limit, a leading-orderin-−1/ log ε analysis, shows that the linear stability problem for localized spot patterns characterizing competition instabilities can be reduced to the study of classes of nonlocal eigenvalue problems (NLEPs) (cf.…”
Section: Parameter Set a Parameter Set Bmentioning
confidence: 99%
See 2 more Smart Citations
“…Li and Bi [31] proposed the enveloping slow-fast analysis that could be used to explain the bursting phenomenon in the system with three time scales. Work about the Brusselator with different time scales, has been found in [8,32]. However, there is little analytical study on the slow-fast phenomenon or its generation mechanism of a Brusselator due to the coupling of the fast and slow subsystems.…”
Section: Introductionmentioning
confidence: 99%